Term and Preterm Children with Cerebral Palsy: Etiology, Clinic and Magnetic Resonance Imaging Findings (Annals of Medical Research, 2021)
Aim: Cerebral palsy (CP) is a frequent neurologic disease of term and preterm neonates. The disorder has various causes and the etiology, clinical manifestations and radiological screening findings are different in term and preterms. Thirty six preterm and 66 term CP patients aged between 6 months-16 years were evaluated in this study and were compared according to their etiology, clinical manifestation and cerebral Magnetic Resonance Imagıng (MRI) findings statistically.
Keywords: Cerebral Palsy, MRI,Term, Preterm